The Existence, Uniqueness and Stability of the Standard System - Blakley, G. R.; Gossling, W. F. (Review of Economic Studies, 1967)
Journal Article The Existence, Uniqueness and Stability of the Standard System Get access G. R. Blakley, G. R. Blakley State University of New York at Buffalo, University of Manchester Search for other works by this author on: Oxford Academic Google Scholar W. F. Gossling W. F. Gossling State University of New York at Buffalo, University of Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 4, October 1967, Pages 427–431, https://doi.org/10.2307/2296563 Published: 01 October 1967